Multidirectional Scratch Detection and Restoration in Digitized Old Images. (13th October 2010) - Ardizzone Ardizzone, E. E.; Dindo Dindo, H. H.; Mazzola Mazzola, G. G.
Abstract : Line scratches are common defects in old archived videos, but similar imperfections may occur in printed images, in most cases by reason of improper handling or inaccurate preservation of the support. Once an image is digitized, its defects become part of that image. Many state-of-the-art papers deal with long, thin, vertical lines in old movie frames, by exploiting both spatial and temporal information. In this paper we aim to face with a more challenging and general problem: the analysis of line scratches in still images, regardless of their orientation, color, and shape. We present a detection/restoration method to process this defect.